KEMITRAAN USAHA SEBAGAI UPAYA MENINGKATKAN DAYA SAING UKM (USAHA KECIL MENENGAH) (STUDI DI PERKAMPUNGAN INDUSTRI KECIL (PIK) JAKARTA TIMUR) - Endang Sri Rahayu (Fakultas Ekonomi Universitas Negeri Jakarta, 2010)
ABSTRACTThis research aimed to analyze the Partnership and Competitiveness of Small and Medium Industri (UKM) in the Small Industrial Township (PIK), East Jakarta Municipality. This research, conducted with survey. The results of this study indicated that there were (1) positive relationships between Partnerships with UKM Competitiveness; (2) Partnerships have proven a significant relationship with the Competitiveness of gaining market; (3) Partnership and Competitiveness has strengths and weaknesses in the face of market.Keyword: Partnership, Competitiveness, UKM